Xerostomia in Dialysis Patients-Oral Care to Reduce Hyposalivation, Dental Biofilms and Gingivitis in Patients with Terminal Renal Insufficiency: A Randomized Clinical Study - Leonie C. Egbring; Tomas Lang; Burkhard Kreft; Karl W. Weich; Peter Gaengler (MDPI AG, 2023)
Objectives: Dialysis patients suffer from xerostomia based on hyposalivation even in stimulated saliva testing. Therefore, the aim of this study was (i) to evaluate an optimized oral hygiene system with an oral care gel reducing oral dryness, supporting dental plaque control and reducing the number of gingivitis affected teeth; (ii) to document the efficacy in a randomized controlled trial with dental indices; and (iii) to record the individual's oral health related quality of life. Methods: After ethical approval (EC-UWH 103/2019), 44 dialysis patients provided signed informed consent and were divided into two groups followed up for four weeks. Subjects of the verum group (A) received daily oral care gel OROFAN® based on biopolymers with a mild antibacterial and saliva stimulating action. They were compared to the control group (B) who executed routine oral hygiene with conventional dentifrice and toothbrushes. At baseline (T0), the medical report and all dental indices (sialometry, DMF/S, plaque index, periodontal index, tongue coating and denture hygiene index) were assessed. After 2 weeks and 4 weeks, T1 and T2 dry mouth frequency and all dental indices were assessed. An Oral Health Impact Profile was documented at baseline (T0) and at the end of the study (T2). Results: Twenty-two subjects were allocated to group A and to group B. At baseline, there were no statistical differences concerning renal insufficiency (years on dialysis and complications), systemic diseases and dental background (caries experience, periodontal diseases, plaque index and number of gingivitis affected teeth). All subjects exhibited hyposalivation (<0.7-1.0 mL/min). The control group (B) showed no statistical differences from baseline (T0) to the end of the study (T2) in dry mouth parameters, in all dental plaque and inflammation indices and in their Oral Health Impact Profile. In contrast, the verum group (A) exhibited a highly significant (p < 0.001) decrease in xerostomia frequency, in the number of gingivitis affected teeth and in their plaque index. Furthermore, their Oral Health Impact Profile improved considerably (p < 0.01). Significance of Results: Terminally ill patients may gain better oral health and, consequently, an improved quality of life by rather simple oral care using long-lasting, edible anti-inflammatory oral hygiene gel and a dentist's devotion.